Weather situation during observed ship-icing events off the coast of Northern Norway and the Svalbard archipelago - Samuelsen, Eirik Mikal; Graversen, Rune (Weather and Climate Extremes, 2019)
Source at https://doi.org/10.1016/j.wace.2019.100200 . Ship icing may lead the ship and crew in great jeopardy. Usually, predictions of such ice build-up are based on the modelling of the heat fluxes capable of freezing sea water originated from wave-ship interactions. This study, on the other hand, follows a different and more general approach by investigating the relationship between the weather situation and icing both using observed parameters from 17 ships operating in Arctic-Norwegian waters from 1980 to 2006, and by applying upper-air parameters derived from NOrwegian ReAnalysis 10 km data (NORA10). In the atmosphere, the memory aloft is larger than that near the surface providing capability of medium-range icing predictions based on such upper-air parameters. It is demonstrated that cold-air outbreak from the ice-covered ocean areas is the dominant weather situation during icing. However, around 10% of the icing events arise in cold-air outbreak mountain-wave situations with downslope windstorms near the coastlines of Northern Norway and Svalbard. It is shown that snow showers and frontal snow, mostly in combination with sea spray, increase the risk of icing. Finally, a simple model applying the temperature and temperature anomaly at 850 hPa is found to be more accurate than methods based on temperature and wind close to the surface. The model is further improved by including wind at 850 hPa.